Party regulation and electoral success: The case of anti-Euro movements - De Petris, Andrea (Ballot, 2015)
The article analyzes the new European protest political parties that want to break away from the European political-economic bloc, which have surprisingly been obtaining more voter support than forecast by political analysts. I examine the party laws of each of the countries and check for the existence of a relationship between the rules on founding new parties in each country and the success of these protest parties. For this purpose, the article is divided into three parts. In the first, I present the main characteristics of some of these parties. In the second, I summarize the types of legal regulation they need to follow in their respective countries. In the third, I analyze the results obtained by them at the polls in the European elections of May 2014. —————- Este artigo fará uma análise dos novos partidos políticos de protesto que pretendem romper com o bloco político-econômico europeu, os quais vêm, surpreendentemente, obtendo mais votos do que o previsto por analistas políticos. Examinarei as leis partidárias de cada um dos países citados no artigo e verificarei se há relação entre as normas pertinentes à fundação de partidos e o sucesso desses partidos de protesto. Para tanto, o artigo será dividido em três partes. Na primeira delas, apresentarei as principais características de alguns desses partidos. Na segunda, farei um resumo dos tipos de regulação legal a serem seguidas pelos partidos em seus respectivos países. Na terceira, analisarei os resultados obtidos por eles nas eleições europeias de 2014.